A novel role for HNO in local and spreading vasodilatation in rat mesenteric resistance arteries. - Yuill, K; Yarova, P; Kemp-Harper, B; Garland, C; Dora, K (2011)
Nitric oxide-mediated vasodilatation has previously been attributed to the uncharged form of the molecule (NO(•)), but increasing evidence suggests that nitroxyl (HNO) may play a significant role in endothelium-dependent relaxation. The aim of this study was to investigate the mechanisms underlying HNO-mediated vasodilatation in phenylephrine pre-constricted pressurized (70 mmHg) mesenteric arteries, and on membrane currents in isolated smooth muscle cells using whole cell and perforated patch clamp recordings. Angeli's salt (AS: nitroxyl donor), evoked concentration-dependent vasodilatation that was insensitive to the NO(•) scavengers carboxy-PTIO and hydroxocobalamin (HXC), but sensitive to either the HNO scavenger L-cysteine, K-channel blockers (4-AP and iberiotoxin), raised [K(+)](o), or inhibition of soluble guanylyl cyclase (ODQ). AS-evoked smooth muscle hyperpolarization significantly augmented K(V) current in an ODQ sensitive manner, and also increased the BK(Ca) current. Importantly, 30 μM AS initiated conducted or spreading vasodilatation, and following blockade of endothelial K-channels (TRAM-34 and apamin), ACh was able to evoke similar L-cysteine-sensitive conducted dilatation. These data show that vasodilatation induced by HNO is mediated by both K(V) and BK(Ca) channels, and suggest a physiological role in vasodilatation through the vasculature.